Variação espaço-temporal na distribuição e abundância de Moenkhausia sanctaefilomenae (Characiformes: Characidae) em lagoas da planície de inundação do rio Cuiabá, Pantanal, Brasil - Lourenco, Luzia da Silva; de Fatima Mateus, Lucia Aparecida; Penha, Jerry (Universidade Estadual de Maringa, 2012)
Identifying the biotic and abiotic factors that determine the variation in the distribution and abundance of populations has become a great challenge for the field of ecology in recent years. Thus, in this study we evaluated the effect of abiotic variables and the abundance of predators on the abundance of Moenkhausia sanctaefilomenae, the variation in the average length of the individuals between lakes and periods, and the effect of the abiotic variables and abundance of predators on the structure in length of that species. Sixteen lakes of the Cuiaba river flood plain were sampled in June (drying period), September (dry period) and December (flooding period) 2005 and March (flood period) 2006. For M. sanctaefilomenae, the distribution is ampler and the abundance is greater at the end of the drying period, beginning of dry season, reducing gradually over the periods of dry, drying and flood season. Additionally, the period affects the structure in size of the populations that are spatially homogeneous. Smaller individuals were captured at the end of the drying period and the larger individuals at the start of flooding. During the end of the drying period and in the beginning of the dry season, the spatial variation in the abundance of the population was positively related with pH, dissolved oxygen and macrophyte cover and area of the lake, but not with the local abundance of predators in the littoral zone of the lakes.
Spatial-temporal variation of the distribution and abundance of Moenkhausia sanctaefilomenae at lagoons of the Cuiaba river floodplain, Pantanal, Brazil.